Further seasonal changes in Uranus' cloud structure observed by Gemini-North and UKIRT - Irwin, P; Teanby, N; Davis, G; Fletcher, L; Orton, G; Calcutt, S; Tice, D; Hurley, J (2012)
Near-infrared observations of Uranus were made in October/November 2010 with the Gemini-North telescope in Hawaii, using NIFS, an integral field spectrograph, and the NIRI instrument in imaging mode. Observations were acquired using adaptive optics and have a spatial resolution of approximately 0.1-0.2'.The observed spectra along Uranus' central meridian were analysed using a multiple-scattering retrieval algorithm to infer the vertical/latitudinal variation in cloud optical depth, which we compare with previous observations made by Gemini-North/NIFS in 2009 and UKIRT/UIST observations made between 2006 and 2008. Assuming a continuous distribution of small particles (r~ 1μm, and refractive index of 1.4. +. 0. i) with the single scattering albedo set to 0.75 and using a Henyey-Greenstein phase function with asymmetry parameter set to 0.7 at all wavelengths and latitudes, the retrieved cloud density profiles show that the north polar zone at 45°N has continued to steadily brighten while the south polar zone at 45°S has continued to fade. As with our previous analyses we find that, assuming that the methane vertical profile is the same at all latitudes, the clouds forming these polar zones at 45°N and 45°S lie at slightly lower pressures than the clouds at more equatorial latitudes. However, we also find that the Gemini data can be reproduced by assuming that the main cloud remains fixed at ~2. bar at all latitudes and adjusting the relative humidity of methane instead. In this case we find that the deep cloud is still more opaque at the equator and at the zones at 45°N and 45°S and shows the same seasonal trends as when the methane humidity remain fixed. However, with this approach the relative humidity of methane is seen to rise sharply from approximately 20% at polar latitudes to values closer to 80% for latitudes equatorward of 45°S and 45°N, consistent with the analysis of 2002 HST observations by Karkoschka and Tomasko (Karkoschka, E., Tomasko, M. [2009]. Icarus 202, 287-302), with a possible indication of seasonal variability. Overall, Uranus appeared to be less convectively active in 2010 than in the previous 4. years, supporting the conclusion that now the northern spring equinox (which occurred in 2007) has passed, the atmosphere is settling back into the more quiescent state seen by Voyager 2 in 1986. © 2011 Elsevier Inc.